Empirical investigation of visualization quality for three-dimensional (3d) objects of 3d map on mobile device for navigation aid - Abubakar, Adamu; Moedjiono, Sardjoeni; Mantoro, Teddy; Zeki, Akram M.; Chiroma, Haruna (Little Lion Scientific Islamabad Pakistan, 2014)

(untitled)
Previous studies have shown some key factors that influence the success of visualization quality for 3D objects of 3D map on Personal computers (PCs) and Laptops’, crucial to that is the 3D computational processing capabilities of PCs and Laptops. Unfortunately 3D applications on mobile devices are hindered by the lack of efficient mobile rendering interfaces, low computational resources and direct 3D rendering at interactive rates. Although recently there are several attempts of building complicated 3D map visualization tasks on mobile devices, yet there is still problem of visualization quality of 3D objects of 3D map on a mobile device, this could be attributed to salient features which this paper try to uncover. An experiment that is aimed at investigating how people visualized 3D objects and orient themselves with the 3D map view on a mobile device for navigation assistance was carried out. The result indicates that the size and shape of 3D objects of 3D map significantly aided orientation, but there are no significant differences between the size and color. The 3D map view can increase the user’s sense of presence; however, 3D map projections tend to represent familiar scenes by collections of their 2D views. This paper shows visual variations of complex 3D map scenes on small-screen mobile devices, with a single object-centered 3D map projection.